1985
DOI: 10.1159/000212725
|View full text |Cite
|
Sign up to set email alerts
|

Dysdifferentiative Nature of Aging: Age-Dependent Expression of MuLV and Globin Genes in Thymus, Liver and Brain in the AKR Mouse Strain

Abstract: The amount and sequence complexity of RNA transcribed by the murine leukemia virus (MuLV) genome and to the α- and β-globin genes in thymus, brain and liver were measured throughout the life span of AKR mice using a cDNA·RNA hybridization technique. RNA complementary to the complete sequence of specific cDNA probes for both MuLV and globin was found in nuclei and cytoplasm of thymus, brain and liver at all ages studied. No significant age-dependent change in the amount or sequence complexity of globin RNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Profiles for the AKR/J strain include high rates of leukemia, which leads to a shortened lifespan [e.g. 90]. Early mortality in the AKR/J group of the present study necessitated conducting the water maze test earlier in the testing sequence, using a second set of mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Profiles for the AKR/J strain include high rates of leukemia, which leads to a shortened lifespan [e.g. 90]. Early mortality in the AKR/J group of the present study necessitated conducting the water maze test earlier in the testing sequence, using a second set of mice.…”
Section: Discussionmentioning
confidence: 99%
“…While the group remained healthy throughout the T-maze testing, eleven of the mice died or were euthanized due to weight loss before the start of the water maze testing, possibly due to the high rate of leukemia reported for this strain (e.g. 90). A separate group of 20 AKR/J mice were tested, using the sequence described above, but with water maze testing conducted at an earlier time point (age 3-4 months), rather than the T-maze test.…”
Section: Test Proceduresmentioning
confidence: 99%
“…Indeed, there appears to be a general correlation between ageing and progressive demethylation of the RTNs [50,51]. Three studies have reported activation of specific, individual RTNs during ageing [52][53][54], one of these [52] involving the activation of a lymphoma-associated HERV.…”
Section: A S Wilkinsmentioning
confidence: 99%
“…These programmed events include, for example, the changes in gene expression associated with the loss of hormonal balance (32,34). We are directing our efforts toward an understanding of the programmed changes in gene expression and metabolism that are normally associated with the process of aging.It has been observed for some time that aging is accompanied by an overall deregulation of gene activity (10,29,30,45). At the same time, several investigators have reported changes in the transcriptional activity of specific genes in several organisms (14,34,35,41,46,47).…”
mentioning
confidence: 99%
“…It has been observed for some time that aging is accompanied by an overall deregulation of gene activity (10,29,30,45). At the same time, several investigators have reported changes in the transcriptional activity of specific genes in several organisms (14,34,35,41,46,47).…”
mentioning
confidence: 99%